Answer:
x = 1
Explanation:
Using the rules of exponents
=
![a^(mn)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/y1umqrf7s4do08xjl3a1y1e5wom5ygzas5.png)
×
⇔
![a^((m+n))](https://img.qammunity.org/2021/formulas/mathematics/middle-school/fxs5lnf7tytk6qj5bfwiird4t7e5ckr338.png)
Note that 9 = 3² and 27 = 3³ , thus
×
![27^(x)](https://img.qammunity.org/2021/formulas/mathematics/high-school/pm362hoycxmz8wuk1w5o4gwrfe8ag2o9xn.png)
=
×
![(3^3)^(x)](https://img.qammunity.org/2021/formulas/mathematics/high-school/3vpvgk8hs5iqwrr8f5x5odclep1a544uty.png)
=
×
![3^(3x)](https://img.qammunity.org/2021/formulas/mathematics/high-school/l8mys2p778ncivm3615f8gfigkvc9mn0bh.png)
=
![3^((2x-4+3x))](https://img.qammunity.org/2021/formulas/mathematics/high-school/fshh70z6i2ojgnvdqra5yel5szem1hq6vj.png)
=
, then
=
![3^(1)](https://img.qammunity.org/2021/formulas/mathematics/college/kxs5i0wbvlp52dpnh2vz1p1t2kopr0w7tl.png)
Since the bases on both sides are equal, equate the exponents
5x - 4 = 1 ( add 4 to both sides )
5x = 5 ( divide both sides by 5 )
x = 1